Personality Characteristics in Female Students with Premenstrual Dysphoric Disorder and Premenstrual Syndrome - Izadi, Maryam; Amiri, Samaneh (Advances in Nursing & Midwifery, 2019)
Abstract premenstrual dysphoric disorder and severe premenstrual syndrome are from prevalent problems in women that cause impairment in many aspects of their life. This research aimed to study personality characteristics of female students with premenstrual syndrome and severe premenstrual dysphoric disorder. The sample of the study consisted of 210 female students of Shahed University in Tehran, Iran. They completed NEO-FFI, Premenstrual Symptoms Screening Tool (PSST) and demographic form. Data were analyzed using MANOVA. 10.2 % of participants suffered from PMDD, 32.1% of participants have PMS and 57.2% were free of symptoms. There were significant differences in neuroticism between students with moderate to severe PMS and PMDD, and students who are free of symptoms or have mild PMS. There was also significant difference in agreeableness between individuals with PMDD and those who are free of symptoms/ have mild PMS. In conclusion, personality characteristics (including Neuroticism and Agreeableness) should be considered as the psychological factors that effect on incident and severity of PMS and PMDD.